Determinants of Oral Health: Does Oral Health Literacy Matter?. (13th March 2013) - Naghibi Sistani, Mohammad Mehdi; Yazdani, Reza; Virtanen, Jorma; Pakdaman, Afsaneh; Murtomaa, Heikki
Abstract : Objective . To evaluate oral health literacy, independent of other oral health determinants, as a risk indicator for self-reported oral health. Methods . A cross-sectional population-based survey conducted in Tehran, Iran. Multiple logistic regression analysis served to estimate the predictive effect of oral health literacy on self-reported oral health status (good versus poor) controlling for socioeconomic and demographic factors and tooth-brushing behavior. Results . In all, among 1031 participants (mean age 36.3 (SD 12.9); 51% female), women reported brushing their teeth more frequently (P < 0.001 ) and scored higher for oral health literacy (mean 10.9 versus 10.2, P < 0.001 ). In the adjusted model, high age (OR = 1.01, 95% CI 1.003–1.034), low education (OR = 1.88, 95% CI 1.23–2.87), small living area in square meters per person (OR = 1.85, 95% CI 1.003–3.423), poor tooth brushing behavior (OR = 3.35, 95% CI 2.02–5.57), and low oral health literacy scores (OR = 1.58, 95% CI 1.02–2.45) were significant risk indicators for poor self-reported oral health. Conclusions . Low oral health literacy level, independent of education and other socioeconomic determinants, was a predictor for poor self-reported oral health and should be considered a vital determinant of oral health in countries with developing health care systems.